Monteverdi a San Marco, eds. Marco di Pasquale, Rodolfo Baroncini, Lucca 2020 - Gembicki, Bartłomiej (Muzyka, 2021)
Recenzja książki: Monteverdi a San Marco. Venezia 1613–1643, red. Marco di Pasquale, Rodolfo Baroncini, Lucca 2020